VD_FINDINFO Arrêt / 2015 / 800 vom 2. November 2015 - VD Tribunal cantonal (2015)
RENTE D'INVALIDITÉ, NOUVELLE DEMANDE, EXPERTISE MÉDICALE | 28 al. 1 LAI, 4 al. 1 LAI, 16 LPGA, 17 LPGA, 6 LPGA, 7 LPGA, 8 LPGA, 87 al. 2 RAI, 87 al. 3 RAI